Managerial Communication System for the Operation of Learning Acceleration Programs - Miftakhul Huda (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2019)
Research on managerial communication in special classes was essential because it has unique characteristics and need specialized administrative too. This study aimed to find out the mixture of communication in the managerial communication system for the implementation of accelerated classes at State Senior High School 3 Surakarta. The type of this research was descriptive qualitative. The research subjects consisted of the school principals, the administrators of the acceleration program, and the parents of accelerated students at State Senior High School 3 Surakarta. The Data collection techniques in this study used interview, observation, and documentation techniques. The mixture of communication, which was consists of four components, those are advertising (socialization), personal sales, sales promotion, and public relations contained in the managerial communication system for the acceleration of learning programs. There were three forms of socialization programs for accelerating programs; visiting schools, maximizing brochures and web utilization. Types of socialization itself include selective demand advertising and indirect socialization. Based on the school's potential, a socialization model can be developed in the form of making school magazines, parent/guardian forums, and holding event activities. Keywords: Managerial Communication System, Operation of Learning Acceleration Programs